Biology community portal [electronic resource] (MERLOT, 2017)
Quoted from the homepage: MERLOT is a spectacular collection of online resources you can access for use in learning and teaching. MERLOT is an initiative of the California State University. The Biology board curates the materials related to life science. We assemble, review, and maintain resources in Anatomy & Physiology, Medicine, General Biology (including subdisciplines such as Botany, Zoology, Evolution, Genetcs, etc.), Biochemistry, Ecology and Environmental Sciences. The materials range from short videos or articles to entire courses. These can be used for learning, teaching, professional development or anything else you can dream up. The Biology board consists of people from institutions across the country who volunteer their time and energy to upkeep and update the amazing collection of resources in the life sciences. Meet the current Biology Board here. We invite you to peruse and use the Biology resources found in MERLOT. You can create a portfolio of materials for use in a class, a project or simply for your own use. If we have reviewed the material you will see a rating and a summary of the review. You can also find comments from people who have used the resource. You can help with the MERLOT project as well by contributing materials (which we will put in our queu to review). If you are interested in joining the Biology board, please contact the editors, Michael Plotkin or Marty Zahn. Our board uses this form for our reviews. Enjoy!